2021
DOI: 10.3390/insects12090785
|View full text |Cite
|
Sign up to set email alerts
|

Fascination and Joy: Emotions Predict Urban Gardeners’ Pro-Pollinator Behaviour

Abstract: The conservation of pollinators requires social understanding to catalyse restoration action. Citizen science (CS) is discussed as a way to promote interest and action for pollinating insects. Yet, the drivers behind pro-pollinator behaviour are largely unclear, especially in urban areas. To better understand public engagement in pollinator conservation, we studied urban community gardeners’ identity, nature-relatedness, emotions, and attitudes toward pollinators and their intentions to get involved in pro-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…While evaluations tend to focus on knowledge and learning outcomes (Peter et al 2019), the results of this study support research showing people are motivated to take part in citizen science projects by a desire to connect to nature (Vasiliades et al 2021), and report psychological and emotional benefits from participating (Schuttler et al 2018). In line with Sturm et al (2021), the research suggests the importance of citizen science projects recognising and utilising people's affective relationship with nature in supporting their participation. This may maximise the psychological benefits they gain from taking part, as well as supporting intention to engage in pro-nature conservation behaviour (Sturm et al 2021).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…While evaluations tend to focus on knowledge and learning outcomes (Peter et al 2019), the results of this study support research showing people are motivated to take part in citizen science projects by a desire to connect to nature (Vasiliades et al 2021), and report psychological and emotional benefits from participating (Schuttler et al 2018). In line with Sturm et al (2021), the research suggests the importance of citizen science projects recognising and utilising people's affective relationship with nature in supporting their participation. This may maximise the psychological benefits they gain from taking part, as well as supporting intention to engage in pro-nature conservation behaviour (Sturm et al 2021).…”
Section: Discussionsupporting
confidence: 75%
“…In line with Sturm et al (2021), the research suggests the importance of citizen science projects recognising and utilising people's affective relationship with nature in supporting their participation. This may maximise the psychological benefits they gain from taking part, as well as supporting intention to engage in pro-nature conservation behaviour (Sturm et al 2021).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We observed intense care and willingness to monitor plant development until the end of the project, even though many gardeners harvested very few fruits from the plants they observed and reported that fruits were stolen by visitors. It seems that the gardeners' motivation to actively engage in pro‐pollinator activities in their gardens, for example by participating in a scientific research project, goes beyond harvest success (Karlebowski et al., in preparation; Sturm et al., 2021). When surveying these gardeners on their motivation to participate in the citizen science project—an indicator of pro‐pollinator behaviour itself—we found the importance of positive nature experiences that are based on nature‐relatedness as well as emotions.…”
Section: Urban Community Gardens Are Spaces For Human‐nature Interact...mentioning
confidence: 99%